2017
DOI: 10.2139/ssrn.3082785
|View full text |Cite
|
Sign up to set email alerts
|

Two Sequencing Problems: Equivalence, Optimal Solution, and State-of-the-Art Results

Abstract: We show that the serial SNPV and the LCFDP are equivalent. The serial SNPV is a special case of the SNPV that tries maximize the expected NPV of a project by sequencing activities that have stochastic durations and cash flows that are incurred at the start of an activity. The LCFDP, on the other hand, minimizes the expected cost of the sequential diagnosis of a set of tests that have known execution costs and failure probabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The author subsequently applied the results to finding the optimal sequence of stages in multistage sequential projects with stochastic stage durations, also obtaining exact, closed-form expressions for the moments of the NPV and using a three-parameter lognormal distribution to approximate the NPV distributions accurately [24]. He showed that the problem is equivalent to the least cost fault detection problem (LCFDP; this was also proven by [25]). Hermans and Leus [26] offered a new efficient algorithm and showed that in Markovian PERT networks, where activities are exponentially distributed and there are no resource constraints, the optimal preemptive solution solves the nonpreemptive case as well.…”
Section: A the Max-npv Problemmentioning
confidence: 97%
See 2 more Smart Citations
“…The author subsequently applied the results to finding the optimal sequence of stages in multistage sequential projects with stochastic stage durations, also obtaining exact, closed-form expressions for the moments of the NPV and using a three-parameter lognormal distribution to approximate the NPV distributions accurately [24]. He showed that the problem is equivalent to the least cost fault detection problem (LCFDP; this was also proven by [25]). Hermans and Leus [26] offered a new efficient algorithm and showed that in Markovian PERT networks, where activities are exponentially distributed and there are no resource constraints, the optimal preemptive solution solves the nonpreemptive case as well.…”
Section: A the Max-npv Problemmentioning
confidence: 97%
“…Constraints (24) bound the flow variables with the maximum resource consumption modes. Finally, constraints (25), which we introduced in [50], determine the value attributes according to the selected modes.…”
Section: The Proposed Mixed Integer Program (Mip) Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, exact expressions in closed form were derived for the moments of NPV, with the utilization of a three-parameter lognormal distribution to accurately approximate the distributions of NPV [69]. Additionally, it was demonstrated that this problem is equivalent to the least-cost fault detection problem, which was established by [69] and [70]. Hermans and Leus [71] contributed to the field by presenting a novel and efficient algorithm.…”
Section: Max-npv Problemmentioning
confidence: 99%